Staffing and training for educational closed-circuit television : report of a joint working party of the National Educational Closed-circuit Television Association and the Association of Cinematograph Television and allied technicians (ITS Working Papers, 1971)
This report is the result of a joint investigation by a working party whose members werw drawn from the national educational closed circuit television association (NECCTA) and the association of cinematograph television and allied technicians (ACTT). The working party was established in may 1970 by the respective organizations and the following terms of reference were agreed.